The Contributions of Community-Based Monitoring and Traditional Knowledge to Arctic Observing Networks: Reflections on the State of the Field - Johnson, Noor; Alessa, Lilian; Behe, Carolina; Danielsen, Finn; Gearheard, Shari; Gofman-Wallingford, Victoria; Kliskey, Andrew; Krümmel, Eva-Maria; Lynch, Amanda; Mustonen, Tero; Pulsifer, Peter; Svoboda, Michael (ARCTIC, 2015)
Community-based monitoring (CBM) in the Arctic is gaining increasing support from a wide range of interested parties, including community members, scientists, government agencies, and funders. Through CBM initiatives, Arctic residents conduct or are involved in ongoing observing and monitoring activities. Arctic Indigenous peoples have been observing the environment for millennia, and CBM often incorporates traditional knowledge, which may be used independently from or in partnership with conventional scientific monitoring methods. Drawing on insights from the first Arctic Observing Summit, we provide an overview of the state of CBM in the Arctic. The CBM approach to monitoring is centered on community needs and interests. It offers fine-grained, local-scale data that are readily accessible to community and municipal decision makers. In spite of these advantages, CBM initiatives remain little documented and are often unconnected to wider networks, with the result that many practitioners lack a clear sense of the field and how best to support its growth and development. CBM initiatives are implemented within legal and governance frameworks that vary significantly both within and among different national contexts. Further documentation of differences and similarities among Arctic communities in relation to observing needs, interests, and legal and institutional capacities will help assess how CBM can contribute to Arctic observing networks. While CBM holds significant potential to meet observing needs of communities, more investment and experimentation are needed to determine how observations and data generated through CBM approaches might effectively inform decision making beyond the community level. Dans l’Arctique, la surveillance communautaire (SC) reçoit un appui de plus en plus grand de la part de nombreuses parties intéressées, dont les membres de la communauté, les scientifiques, les organismes gouvernementaux et les bailleurs de fonds. Dans le cadre des initiatives de SC, des habitants de l’Arctique ...